Particle Size Effect on Optical and Gas-Sensing Properties of La0.67Ca0.2Ba0.13Fe0.97M0.03O3 (M = Ti4+, Mn3+, and Cr3+) Compounds - Ahmed Dhahri; H. Saoudi; S. R. Gavinho; A. Benali; N. Abdelmoula; R. Dhahri; Lin Peng; Jiangtao Wu; J. Pina; B. F. O. Costa (Crystals, 2024)
In the present work, the morphological, optical, and gas-sensing properties of La0.67Ca0.2Ba0.13Fe0.97M0.03O3 (M = Ti, Cr, and Mn) nano-powders prepared via the auto-combustion route, were investigated. TEM images prove the nanoscale particle size of all the samples. Optical studies confirm the semiconductor behavior of the studied materials. The response of the prepared nano-powders towards the presence of two gas-reducing agents (ethanol and acetone) was investigated. From the resistance ratio under air and gas, it was possible to determine the response to different gases and deduce that La0.67Ca0.2Ba0.13Fe0.97Ti0.03O3 presents the highest responses to ethanol and acetone. Likewise, we deduced that the prepared materials were able to detect low concentrations of ethanol and acetone gases.